2004
DOI: 10.1890/03-0279
|View full text |Cite
|
Sign up to set email alerts
|

Physical Stress and Biological Control Regulate the Producer–consumer Balance in Intertidal Biofilms

Abstract: Epilithic biofilms play a key role in marine ecosystems. They also provide a tractable system to investigate the relative roles of environmental stressors, bottom-up physicochemical factors and top-down biological control in regulating communities. Patterns of photosynthetic microbial biomass were recorded over a four-year period at several tidal levels on shores in the Isle of Man. Photosynthetic biomass and the abundance of diatoms were consistently greater during winter than summer. Biomass was negatively c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
155
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(167 citation statements)
references
References 35 publications
7
155
2
1
Order By: Relevance
“…Phylotype richness increased at all four artificial reefs sampled, with the exception of the last sampling period (July 2011). As the fungal biofilm community matures, an interactive successional stage can occur, allowing new species to recruit while competition and changes in physical habitat may cause less well-adapted species to be lost from the community (Jackson 2003, Thompson et al 2004.…”
Section: Discussionmentioning
confidence: 99%
“…Phylotype richness increased at all four artificial reefs sampled, with the exception of the last sampling period (July 2011). As the fungal biofilm community matures, an interactive successional stage can occur, allowing new species to recruit while competition and changes in physical habitat may cause less well-adapted species to be lost from the community (Jackson 2003, Thompson et al 2004.…”
Section: Discussionmentioning
confidence: 99%
“…While experimental assays have shown that different macroalgae can respond positively to pulsed nutrient additions, especially to phosphate and ammonium (e.g. Lapointe, 1985Lapointe, , 1987Schaffelke and Klumpp, 1998a,b), little is known on the general effects of nutrient inputs along most shores of the world (but see Thompson et al, 2004 for processes controlling biofilms), despite their likely importance to fuel up biological interactions along intertidal coastlines.…”
Section: Introductionmentioning
confidence: 99%
“…Although cyanobacteria appeared generally resistant to experimental treatments, consistently with the almost ubiquitous distribution of microbial biofilms in aquatic systems (Underwood 1984, Hill & Hawkins 1991, Bustamante et al 1995, Costerton et al 1995, differences in macroalgal cover and in the intensity of grazing might have also played a role in determining the different responses of this taxon between the 2 experimental trials (Jenkins et al 1999, Harley & Helmuth 2003, Thompson et al 2004. In particular, the slight increase in abundance of cyanobacteria on cores transplanted to higher heights on the shore in Expt 1 could be ascribed to their release from grazing by limpets, while in Expt 2, where limpets were naturally less abundant, the strength of negative effects could have been increased due to the greater abundance of filamentous and turf-forming algae, such as Laurencia obtusa and Chondrya boryana.…”
Section: Discussionmentioning
confidence: 88%